The Effect of Parental Involvement on Stuents’ Academic Achievement Through Independent Learning Ability - Andi Hana Rafiah Nurhalimah; Viona Djuliarta; Ujang Nurhidayat (JEES: Journal of Education and Educational Sciences, 2025)
This research examines the impact of parental engagement on children’s academic development. Parental involvement is conceptualized through three primary dimensions: attendance at school-related meetings, provision of educational support within the home environment, and active participation in school-based activities. The study seeks to investigate how these facets of involvement influence students’ academic performance, aiming to test a set of predetermined hypotheses through a structured questionnaire-based survey. To assess the interrelationships among the variables, the study utilizes the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The analytical model delineates the association between parental engagement and students’ scholastic achievement, while also illustrating the influence of structured learning processes and the underlying factors driving parental involvement on academic outcomes. Furthermore, anecdotal evidence pertaining to students’ academic attainment substantiates the theoretical framework, emphasizing the interconnected roles of parental involvement, academic performance, and the mediating function of students’ self-regulated learning capabilities. The findings of this research are anticipated to yield valuable insights for enhancing educational outcomes. The primary aim is to investigate the determinants of parental involvement and its effect on academic achievement, with a specific focus on the mediating role of students’ self-regulatory learning skills, as assessed through the PLS-SEM methodology.